Chemical Structure and Localization of Levan, the Predominant Fructan Type in Underground Systems of Gomphrena marginata (Amaranthaceae) - Joaquim, Emanuela O.; Hayashi, Adriana H.; Torres, Luce M. B.; Figueiredo-Ribeiro, Rita C. L.; Shiomi, Norio; de Sousa, Fernanda S.; Lago, João H. G.; Carvalho, Maria A. M. (Frontiers in Plant Science, 2018)
Gomphrena marginata Seub. (Amaranthaceae) is an endemic species from Brazilian campos rupestres. Previous studies suggested that the reserve carbohydrate present in the underground system of this species could be levan-type fructans, similar to that identified in G. macrocephala. High performance anion exchange chromatography (HPAEC–PAD) revealed the presence of the soluble carbohydrates glucose, fructose, sucrose, 1-kestose, 6-kestose, nystose and fructans with degree of polymerization up to approximately 50 fructose units. Two-dimensional nuclear magnetic resonance spectroscopy (2D NMR), HSQC (heteronuclear single-quantum correlation) and HMBC (heretonuclear multiple-bonds correlation) data showed the predominance of levan-type fructans, a linear molecule with β- 2,6 linkages, based on 6-kestose, corroborating with the results previously shown. Structural analyses of the underground system using light microscopy revealed mainly a gemmiferous tuberous root with the upper region formed by short stems, both presenting vascular cylinders with unusual growth patterns. Fructan spherocrystals were visualized under polarized light and SEM mostly in the cortex and vascular cylinder. In addition to data reported in the literature concerning the Amaranthaceae, the results presented here suggest that fructans are a trait in this family while the levan-type fructan prevail in Gomphrena species.